FORMULATION AND ANTIBACTERIAL ACTIVITY TEST OF TOOTHPASTE ETHYL ASETATE FRACTION OF LEILEM LEAVES (Clerodendrum minahassae L.) AGAINTS Streptococcus mutans - Anggun Ciquita Nichelse Egam; Hosea Edy; Surya Sumantri Abdullah (UNIVERSITAS SAM RATULANGI, 2023)
Leilem leaves (Clerodendrum minahassae L.) is one type of plant that can be used as an antibacterial because it contains active chemical compounds such as phenols, flavonoids, alkaloids, steroids, and terpenoids. This study aimed to formulate the ethyl acetate fraction of leilem leaves toothpaste that is physically good and to obtain the optimum toothpaste inhibition with dosage concentrations of 7.5%, 10%, and 12.5% against the growth of Streptococcus mutans bacteria. This research uses laboratory experimental method. The results showed that the ethyl acetate fraction toothpaste preparation filled the physical evaluation requirements, that is organoleptic, homogeneity, spreadability, adhesion and pH. The antibacterial activity testing of the leilem leaves fraction toothpaste showed that the average diameter for F1 was 9.75 mm, F2 was 11.75 mm, and F3 was 13.08 mm. Based on the results of the study, it can be concluded that all formulations of the ethyl acetate fraction of leilem leaves provide antibacterial activity and filled the requirements of the physical test of the preparation and the greatest antibacterial activity is at F3 of 13.08 mm with a dosage concentration of 12.5%.